The Effect of Using Podcast toward Students’ Listening Skill - Ghina Muthi'ah Azmi (Foremost Journal, 2021)
ABSTRACT This   research   was   conducted   at   SMK   Lab   Business   School Kota   Tangerang.   The   aim   was   to   know   whether   there   is   a significant    effect    of    using    Podcast    to    improve    students' listening   skill.   The   population   of   this   research   was   eleventh grade  students  of  SMK  Lab  Business  School  Kota  Tangerang. The  sample  are  37  students  of  11  AP  2.  This  research  used Quasi-Experimental.   The   data   was   collected   by   pre-test   and post-test.     The     statistical     calculation     of     the     one-sample Kolmogorov-Smirnov test was the result of this research; the asymptotic   significance   of   the   pre-test   and   post-test   in   the experimental   class   data   is   0.000   <   0.05.It   can   be   concluded that   Ha   is accepted   and H0 is rejected. It means that the use of podcast  on  listening  skill  makes  a  significant  difference.  It  can also   be   concluded   that   the   Media   Podcast   has   a   positive impact  on  listening  skills  in  the  eleventh  grade  of  SMK  Lab Business    School    Kota    Tangerang    in    the    academic    year 2020/2021.